Fit for purpose? Using the fit note with patients with chronic pain: a qualitative study - Wainwright, Elaine (Royal College of General Practitioners, 2011)
BACKGROUND: Staying in work may benefit patients with chronic pain, but can be difficult for GPs to negotiate with patients and their employers. The new fit note is designed to help this process, but little is known of how it is operating. AIM: To explore GPs' views on the fit note, with particular reference to sickness certification for patients with chronic pain. DESIGN AND SETTING: Qualitative study using semi-structured interviews in eight primary care trusts in south-west England. METHOD: In-depth interviews with 13 GPs. RESULTS: GPs reported that the rationale behind the fit note is sound and that it may help patients with chronic pain to return to work earlier. However, GPs also reported barriers to successful fit note use, including the need to preserve doctor–patient relationships, inconsistent engagement from employers, GPs' lack of specialist occupational health knowledge, issues with fit note training, and whether a new form can achieve cultural shift. CONCLUSION: While doctors agree that good work improves health outcomes, they do not think that fit notes will greatly alter sickness-certification rates without more concerted initiatives to manage the tripartite negotiation between doctor, patient, and employer.